ASEAN Role in Asia-Pacific Regional Architecture Building - S. M. Menshikova (Vestnik MGIMO-Universiteta, 2012)
The collapse of the bipolar system caused significant transformations in world’s political and strategic balance of powers, particularly had an impact on the Asia- Pacific nations and created “political vacuum” in the region. In Asia-Pacific crash of the bipolar confrontation stimulated internal processes. Mostly «vacuum» was filled by ASEANcentered new regional architecture.